Quality Characteristics and Ultra Structural Changes of Restructured Buffalo Meat Slices with Flaxseed Flour as Binder: A Novel Value Added Technology - Bhaskar Reddy, G.V.; Viswa natha Reddy, K.; P, Amaravathi (Emirates Journal of Food and Agriculture, 2023)
In India, spent buffaloes are the main contributors of meat, which is tough and low priced and poor demand in the market. In this context, a new technological intervention is needed for restructuring of meat to enhance value-added meat production. Accordingly, an investigation was carried out to analyze the efficacy of different levels of flaxseed flour (C, T1, T2, and T3) as a novel binder for making of Restructured Buffalo Meat Slices (RBMS). The results revealed that T3 (RBMS added with 6% flaxseed flour) demonstrated significantly (P<0.01) higher cooking yield, water-holding capacity (WHC), batter stability and lower diameter shrinkage than control and RBMS incorporated with 2 % and 4 % flax seed flour. None of the treatments had significant influence on pH, total protein extractability, collagen content and solubility of RBMS. Moreover, T3 revealed significantly (P<0.01) higher moisture, total protein, total fat and total ash content than RBMS formulated with other levels of flax seed flour. Conversely, significantly lower in hardness, springiness, chewiness and higher in cohesiveness than other treatments. However, T3 influenced the colour scores, though at different degrees. Ultra structural images of cooked samples displayed the protein matrix between myofibrils which indicates gel network of flaxseed gum and proteins, subsequently caused more cohesiveness. This implies that the flaxseed flour acted as excellent novel binder for binding meat pieces. T3 has proven significantly greater sensory scores than other treatments. Thus, it is clearly evident that T3 has improved most of the quality attributes of buffalo meat and can be recommended as a novel value added technology for meat industry. Keywords: Buffalo meat; Flaxseed flour; Quality characteristics; Restructuring; Ultra structure